THE IMPACT OF COLORS ON SOCIETY - "HOLI PARITY CELEBRATION": रंगों का समाज पर प्रभाव - ”होली समता का उत्सव“ - Arnde, Kishore (International Journal of Research -GRANTHAALAYAH, 2014)
Holi may come from year to year, but the wait for it never diminishes. This festival of getting drenched in colors is our pride festival since ancient times. The color of Holi is such that it has broken the barricades of cults and sects with great fanfare while showering love. The colors of Holi rose on Yayawar Alberuni in such a way that he made special mention of Holikotsav in the memoir of his historical journey. Holi description of Muslim poets is interesting. Sufi saints Hazrat Nizamuddin Auliya, Amir Khusro and Nazir Akbarabadi have dedicated great creations in the name of Holi. Mughal emperors have also made a big splash of Holi. In Akbar’s palace, large silver-gold pieces of Tesu were paired with kevade and saffron, in Jahangir’s ’Mahfil-e-Holi’ the general public could also cast a color on the emperor. Shah Jahan’s Holi was popularly known as Eid-e-Pink and "Ab-e-Pashi". In festive societies it is a custom to celebrate the beginning of the year enthusiastically. Holi is not just a celebration of colors. It is first a social ritual. If Diwali is a celebration of prosperity for us, Holi is a celebration of equality. होली भले ही साल-दर-साल आती रहे, पर उसके इंतजार की बेकरारी दिलों में कभी कम नहीं होती। रंगों में सराबोर हो उठने का यह त्यौहार प्राचीन काल से ही हमारा गौरव पर्व है। होली की रंगत ही कुछ ऐसी है कि इसने पंथों, संप्रदायों के बाड़ भी प्रेम की बौछार करते हुए बड़े खिलंदड़पन के साथ तोड़े है। यायावर अलबरूनी पर होली के रंग ऐसे चढ़े कि उसने अपनी ऐतिहासिक यात्रा के संस्मरण में होलिकोत्सव का खास जिक्र किया। मुस्लिम कवियों का होली वर्णन दिलचस्प है। सूफी संत हजरत निजामुद्दीन औलिया, अमीर खुसरो व नजीर अकबराबादी ने होली के नाम उम्दा रचनाएँ समर्पित की है। मुगल बादशाहों ने भी होली की खूब धूम मचाई है। अकबर के महल में सोने चांदी के बड़े-बड़े होदों में केवड़े और केसर के साथ टेसू का रंग घोला जाता था, जहांगीर के ‘महफिल-ए-होली‘ में आम जनता बादशाह पर भी रंग उड़ेल सकती थी। शाहजहां की होली, ईद-ए-गुलाबी और “आब-ए-पाशी“ के नाम से मशहूर थी। उत्सवप्रिय समाजों में वर्ष का आरंभ उत्साहपूर्वक मनाने की प्रथा है। ‘होली‘ केवल ‘रंगों‘ का उत्सव नहीं है। वह सबसे पहले एक सामाजिक अनुष्ठान है। दीवाली अगर हमारे लिए समृद्धि का उत्सव है तो होली समता का उत्सव है।